How Do Commercial Children’s Foods Influence Their Growth and Development? A Map of Commercially Available Children’s Foods in Honduras - Santana H., Adriana (Zamorano: Escuela Agrícola Panamericana, 2019., 2019)
The premature consumption of processed foods with high sugar and sodium content over the course of life has been associated with an increased risk of suffering from chronic diseases starting in adolescence or early adulthood. Methods: There was an examination of the nutritional labelling of processed products for young children (n = 140) available in the Honduran market to evaluate their nutritional quality with regard to sodium and sugar content, pursuant to various international recommendations. Results: 54% of the products evaluated derive more than 20% of their calories from sugar. The categories that to a large degree exceed the recommended sugar content range are fruit drinks (80%) and dessert purees (65%). The average price per product serving is lower than one US dollar ($0.81). 46% and 6% of the products place sugar and salt, respectively, among the first five positions in their ingredient lists. Conclusions: Processed foods for infants and young children generally exceed the recommended sugar content, but due to their low cost and easy access, they are displacing traditional food consumption, contributing to increasing childhood obesity and chronic disease in the early stages of life.
Keywords: Fast Foods; Sugar; Infant; Children; Sodium